2010
DOI: 10.1111/j.1365-2648.2010.05471.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary nursing staff - cost and quality issues

Abstract: Ward managers need to monitor temporary staffing and the effect they have on nursing activity and quality. Similar studies in mental health, learning disability and community nursing would generate additional insights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 22 publications
0
69
0
Order By: Relevance
“…25 Data collection instruments (developed for hospices) were piloted in autumn 2008, in two inpatient units. Modifications included: (i) adding dependency scoring criteria for controlled drugs and psycho-social support; (ii) removing/ adding activity categories specific to either general hospital and/or palliative care respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Data collection instruments (developed for hospices) were piloted in autumn 2008, in two inpatient units. Modifications included: (i) adding dependency scoring criteria for controlled drugs and psycho-social support; (ii) removing/ adding activity categories specific to either general hospital and/or palliative care respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The NHS palliative care wards (also 'volunteers'), on the other hand, were already in the broader study. 25 We have not identified our wards owing to the sensitive performance data we report. However, hospice/palliative care staff in each site were given bespoke reports that benchmarked their data without naming the other wards against which they were compared.…”
Section: Samplementioning
confidence: 99%
“…If external labour or agency nurses had been hired for every actualised floating shift, the estimated costs for the hospital would have been much higher (Adams et al 2015, Hurst andSmith 2011). This calculation does not take into account any bonuses paid to individual nurses, which could be awarded on the basis of the number of hours worked or level of professional experience.…”
Section: Financial Implicationsmentioning
confidence: 99%
“…The most common way to manage unstaffed shifts is to use supplemental nurses, such as agency or temporary staff (Adams et al 2015, Xue et al 2015, but this will depend on a hospital's financial resources and is not a cost-effective solution (Hurst andSmith 2011, Adams et al 2015). Interestingly, Xue et al (2015) found that there were no significant differences between the costs of agency nurses and permanent nurses, if the…”
mentioning
confidence: 99%
“…Most organizations use recruitment agencies to hire temporary staff. However, in a recent study on the cost of hiring temporary nursing staff, Hurst and Smith [13] discovered that wards that use both temporary and permanent staff together were more expensive to run while the working styles were quite different.…”
Section: Recruitment and Selectionmentioning
confidence: 99%